Activated keratinocytes in the epidermis of hypertrophic scars. - Machesney, M. (1998)
The etiology of hypertrophic scarring, a pathological end point of wound healing, is unknown. The scars most commonly occur when epithelialization has been delayed during, for example, the healing of deep dermal burn wounds. Hypertrophic scars are conventionally described as a dermal pathology in which the epidermis has only a passive role. In this study, the expression of keratin intermediate filament proteins and filaggrin has been investigated in the epidermis of hypertrophic scars and site-matched controls from the same patients. Hypertrophic scar epidermis was found to express the hyperproliferative keratins K6 and K16 in interfollicular epidermis in association with K17 and precocious expression of filaggrin. K16 mRNA was localized by in situ hybridization using a highly specific cRNA probe. In contrast to the immunohistochemical location of K16 protein, the K16 mRNA was found to be expressed in the basal cell layer of normal skin. In hypertrophic scars the mRNA distribution corroborated the abnormal K16 protein distribution. These results suggest the keratinocytes in hypertrophic scar epidermis have entered an alternative differentiation pathway and are expressing an activated phenotype. Activated keratinocytes are a feature of the early stages of wound healing producing growth factors that influence fibroblasts, endothelial cells, and the inflammatory response. We propose that cellular mechanisms in the pathogenesis of hypertrophic scarring are more complex than isolated dermal phenomena. The persistence of activated keratinocytes in hypertrophic scar epidermis implicates abnormal epidermal-mesenchymal interactions.